Horizontes do perdão: reflexões a partir de Paul Ricoeur e Jacques Derrida - Migliori, Maria Luci Buff (2007)
This workpiece develops a cartography of forgiveness dimensions, encompassing the branches of law, ethic, politics, Christian theology and therapy. It takes profit of Paul Ricoeur s and Jacques Derrida s readings. Forgiveness place is a border place that communicates with a variety of domains. Its discussion involves that of guiltiness and reconciliation with past. The thesis intends to analyze the ethical inscription of forgiveness in philosophy, appointing that this issue requires an incursion in the nonphilosophic field. It adopts as a model the work of the Truth and Reconciliation Commission in South Africa, an experience of reconciliation through a conditional amnesty and a new model of restorative Justice. Some applications of forgiveness spirit in law highlight obligation and responsibility relations, supported by the concept of debt and equivalence applied by Justice. They bring the context of the initial debate about crimes against humanity, after the Second World War, and its relations to the Statement of Rights. According to Ricoeur s view, forgiveness inscription lies in the abundance of non-realized evil. Ricoeur s difficult forgiveness equation reveals the dynamics emerging from the disproportion between the height of learned hymn and guiltiness depth, its imputability and the problematic of incapability. Derrida s reflection about the forgiveness and the unforgivable, in the geopolitical scene, explores the ideas of conditional forgiveness, pure forgiveness and circulation between hyperbolical ethic and politics. The public debate upon the interpretation and reach of Amnesty Law in 1979, promulgated under military dictatorship in Brazil, is an opportunity to appreciate the abuse of forgetter and the need of not erasing the facts, even though debt has been broken up